The The Behavioral Determinants of Health In Housewife For Monitoring of Blood Glucose, Uric Acid, and Cholesterol Level - Moh Fairuz Abadi (Health and Technology Journal (HTechJ), 2023)
Indonesia is a country with a low level of participation in routine health checks, one of which is influenced by gender issues. An independent survey involving 9,612 respondents from all over Indonesia stated that 70% of Indonesians had never done a blood test. Housewives are considered unemployed, and they are considered to have no behavioral strength to decide independently about their health needs. This research aims to analyze the determinants of health behavior that influence housewives for routine monitoring of blood glucose, uric acid, and cholesterol level. This research method is an observational correlation, with a cross-sectional approach where researchers use questionnaires to 22 respondents (housewives) using purposive sampling. The results indicate that the support of people around is significant to the behavior of routine monitoring of blood glucose, uric acid, and cholesterol levels in housewives (p= 0.035; p<0.05). Meanwhile, attitude towards and ease of access is insignificant (p>0.05). The support of people around is crucial in fostering a consistent habit of monitoring blood glucose, uric acid, and cholesterol levels among housewives.